1999
DOI: 10.1111/j.1439-0531.1999.tb01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Aspects of Uterine Involution in the Cow

Abstract: The postpartum period (PP) (querperium) is characterized by involution of the uterus and recyclicity of the ovarian functions to prepare the animal for a new pregnancy period. The time required for the genital organs to become normalised is influenced by breed, management including feeding regimens and environmental factors. This period is also strongly influenced by periparturient diseases such as dystocia, paresis (puerperalis), mastitis, endometritis, etc. The period is also influenced by several hormonal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…In contrast, uterus inflammation stimulates the production of prostaglandins and activates arachidonic acid cascade (Kindahl et al, ; Mishra & Prakash, ). Thereby, plasma PGFM concentration in cows with endometritis after calving is maintained at high levels and decreases slowly to basal levels (Kindahl et al, ; Mishra & Prakash, ). In addition, Sheldon et al () showed that uterine infection after calving delayed the resumption of ovarian function in postpartum dairy cows, because bacterial contamination of the uterus suppressed dominant follicle growth and function.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, uterus inflammation stimulates the production of prostaglandins and activates arachidonic acid cascade (Kindahl et al, ; Mishra & Prakash, ). Thereby, plasma PGFM concentration in cows with endometritis after calving is maintained at high levels and decreases slowly to basal levels (Kindahl et al, ; Mishra & Prakash, ). In addition, Sheldon et al () showed that uterine infection after calving delayed the resumption of ovarian function in postpartum dairy cows, because bacterial contamination of the uterus suppressed dominant follicle growth and function.…”
Section: Discussionmentioning
confidence: 99%
“…(1 Uninfected (n = 21) 9.2 ± 0.5 5.2 ± 0.5 (n = 14) 7.0 ± 0.4 2.9 ± 0.4 42 scEndo (n = 12) 9.9 ± 0.6 5.9 ± 0.6 (n = 10) 7.7 ± 0.5 3.6 ± 0.5 d Uninfected (n = 22) 11.4 ± 0.5 7.4 ± 0.5 (n = 17) 7.9 ± 0.4 3.9 ± 0.4 63 scEndo (n = 15) 11.7 ± 0.6 7.7 ± 0.6 (n = 10) 7.7 ± 0.5 3.7 ± 0.5 Uterine involution is normally assumed to be completed by 4 to 5 wk postpartum (Kindahl et al, 1999). Hence, rebreeding is not recommended before 6 wk postpartum and so d 42 was chosen in this study as an optimal time to evaluate the effects of uterine health on ovarian follicular environment.…”
Section: Dötiiciiö -H-h-h-h-h-h-+1-h-h-h-h-h-h-hmentioning
confidence: 99%
“…Therefore, our search regarding the potential mechanisms underlying the smaller gravid horn and uterine body on d 14 focused on the health condition of the reproductive tract. Kindahl et al (1999) suggested a relationship between uterine health status and PGF 2α levels by indicating that pulsatile elevations of PGF 2α are negatively correlated with involution time in normal cows and positively correlated in cows with endometritis and retained placenta. Prostaglandin F 2α plays an important role in expediting postpartum uterine involution as well as clearing the fetal remnants and birth canal-ascended bacteria in the reproductive tract due to its efficacy in stimulating myometrial contractions.…”
Section: Discussionmentioning
confidence: 95%